Cap‐binding complex assists RNA polymerase II transcription in plant salt stress response. (12th July 2022) - Zhang, Huairen; Li, Xiaoyi; Song, Ruitian; Zhan, Zhenping; Zhao, Fengyue; Li, Zicong; Jiang, Danhua
Abstract: Adaptive response to stress involves an extensive reprogramming of gene expression. Under stressful conditions, the induction of efficient changes in messenger RNA (mRNA) production is crucial for maximized plant survival. Transcription and pre‐mRNA processing are two closely related steps in mRNA biogenesis, yet how they are controlled in plant stress response remains elusive. Here, we show that the Arabidopsis nuclear cap‐binding complex (CBC) component CBP20 directly interacts with ELF7, a subunit of the transcription elongation factor RNA Pol II‐associated factor 1 complex (PAF1c) to promote RNA Pol II transcription in plant response to salt stress. CBP20 and ELF7 coregulate the expression of a large number of genes including those crucial for salt tolerance. Both CBP20 and ELF7 are required for enhanced RNA Pol II elongation at salt‐activated genes. Though CBP20 also regulates intron splicing, this function is largely independent of ELF7. Our study reveals the function of an RNA processing regulator CBC in assisting efficient RNA Pol II transcription and pinpoints the complex roles of CBC on mRNA production in plant salt stress resistance.